Food as Medicine: Can nutrition be a prescription? - Andrea Krenek; Anne Mathews; Wendy Dahl (EDIS)
Diet and lifestyle behaviors can affect health status and the development of disease. The importance of nutrition in healthcare is especially relevant as one in five deaths globally can be connected to poor diet. Food can be an integral part of preventing, managing, and treating disease through personalized nutrition, medically tailored meals and groceries, produce prescription programs, and culinary medicine. This publication dives into how nutrients connect to disease and uses of Food as Medicine as an overview for general learners.